Developing Young Leaders: Integrated Leadership in Volleyball Practice for Positive Youth Development - Hidayat; Afridawati; Adang Suherman; Amung Ma'mun; Nurlan Kusmaedi (Universitas Negeri Semarang, 2025)
The purpose of the research is to determine the development of leadership abilities through a volleyball practice program that is integrated with leadership for positive youth development. The method used is Quasi Experiment Design with The Matching-Only Pre-test-Post-test Control Group Design. The research population consists of school volleyball clubs in Garut Regency which are divided into three groups: 1) a group that takes part in volleyball training with integrated leadership; 2) a group that takes part in volleyball training without leadership integration; and 3) a group that does not participate in volleyball training and is not integrated with leadership. The research samples are teenagers aged 12-25. The instrument used is the Inventory Leadership Identity (ILI). The average pretest score of group A is 43.93, and the average posttest score is 88.48. For group B, the average pretest score was 38.40, with the same average posttest score of 41.48. As for group C, the average pretest score was 25.54, and the average posttest score was 26.08. Based on the results of data processing and analysis, it proves that the group that took part in volleyball training with leadership integration shows a better leadership development for the structured and intentional leadership program.